Late Cenozoic Geology and the Second Oldest Profession - Chesworth, Ward (Geoscience Canada, 1982)
Abstract All soils that are now farmed have beenformed or modified by late Cenozoicevents. Where these events have beendramatic with glaciers and plate tectonicprocesses actively intervening, old soilshave been obliterated and replaced bynewer, inherently more fertile materials.In more placid regions, soils that origi-nated on Tertiary and even Mesozoic land-scapes persist, and continue to evolvetowards states of low fertility. The inhe-rent fertility of soil, a renewable resource,is largely ignored in modern mechanisedagriculture in favour of chemicalfertilizers largely mined from non-renew-able deposits. A saner attitude onceexisted, still exists in at least part of theThird World, and should be re-examinedas a possible basis for future strategies.